Angiotensin II increases respiratory rhythmic activity in the preBötzinger complex without inducing astroglial calcium signaling - Tacke, Charlotte; Bischoff, Anne M.; Harb, Ali; Vafadari, Behnam; Hülsmann, Swen (Frontiers in Cellular Neuroscience, 2023)
Angiotensin II (Ang II) is the primary modulator of the renin-angiotensin system and has been widely studied for its effect on the cardiovascular system. While a few studies have also indicated an involvement of Ang II in the regulation of breathing, very little is known in this regard and its effect on brainstem respiratory regions such as the preBötzinger complex (preBötC), the kernel for inspiratory rhythm generation, has not been investigated yet. This study reports that Ang II temporarily increases phrenic nerve activity in the working heart-brainstem preparation, indicating higher central respiratory drive. Previous studies have shown that the carotid body is involved in mediating this effect and we revealed that the preBötC also plays a part, using acute slices of the brainstem. It appears that Ang II is increasing the respiratory drive in an AT1R-dependent manner by optimizing the interaction of inhibitory and excitatory neurons of the preBötC. Thus, Ang II-mediated effects on the preBötC are potentially involved in dysregulating breathing in patients with acute lung injury.